Non-steroidal anti-inflammatory drug user profile in Chiclayo and Cajamarca, Peru - Mendoza Urrutia, Luis Antonio (2018)
Introduction: Non-steroidal anti-inflammatory drugs (NSAIDs) are frequently and extensively used by many people, and some complications may arise to their frequent and inappropriate use.Objectives: To determine the profile of NSAID consumers (outpatients) in Chiclayo and Cajamarca.Material and Method: A descriptive, prospective and cross-sectional study. 610 outpatients who were NSAID users were assessed in Chiclayo and Cajamarca. Data collection was performed using direct interviews. Data was coded in an Excel database, and it was analyzed using the SPSS statistical software.Results: The average age of interviewed persons was 31,8 years in Chiclayo and 32,7 years in Cajamarca. The most frequently used NSAID in Cajamarca was ibuprofen (44,3%), while in Chiclayo this drug was used by 27,5% of the interviewees; the difference was statistically significant (p= 0,000). Most frequently used NSAID in Chiclayo was naproxen (34,4%), and in Cajamarca naproxen was used by 21,1% of the interviewees, reaching statistically significant difference. The frequency of using a combination including naproxen and ibuprofen was 4,3% in Chiclayo and 2,3% in Cajamarca, with p reaching 0,000. The use of a NSAID with an antibiotic was frequent in both cities: 30,5% in Chiclayo and 24,9% in Cajamarca. Self-medication (46,7% in Chiclayo and 47,9% in Cajamarca) and purchasing the drug with no medical prescription were quite frequent (76,3% in Chiclayo and 65,1% in Cajamarca). When assessing the reasons for using NSAIDs: 37% of interviewees in Chiclayo and 21,3% in Cajamarca reported using these drugs because of the occurrence of general non-specific symptoms. With respect to the frequency of use, 70,2% interviewees in Chiclayo and 76,1% in Cajamarca reported using 1 to 15 tablets per year.Conclusions: The profile of NSAID consumers in Chiclayo and Cajamarca corresponds to young adults taking the so-called "classical" NSAIDs because of the occurrence of non-specific symptoms, and they generally purchase these drugs without a medical prescription (71%); and also, it is not unusual that NSAIDs are combined with antibiotics (25%).